2004
DOI: 10.1021/ja049373g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Evidence for Homogeneous Catalysis in the Gas-Phase Reaction of SiH2 with H2O (and D2O):  A Combined Kinetic and Quantum Chemical Study

Abstract: Time-resolved kinetic studies of the reaction of silylene, SiH(2), with H(2)O and with D(2)O have been carried out in the gas phase at 297 K and at 345 K, using laser flash photolysis to generate and monitor SiH(2). The reaction was studied independently as a function of H(2)O (or D(2)O) and SF(6) (bath gas) pressures. At a fixed pressure of SF(6) (5 Torr), [SiH(2)] decay constants, k(obs), showed a quadratic dependence on [H(2)O] or [D(2)O]. At a fixed pressure of H(2)O or D(2)O, k(obs) values were strongly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 38 publications
(117 reference statements)
12
55
0
Order By: Relevance
“…The true values for the second order rate constants of this reaction are almost certainly smaller than we are observing probably by as much as an order of magnitude (at 10 Torr). It is also probable that a catalysed process, involving two molecules of NH 3 , by analogy with findings in the SiH 2 +H 2 O reaction system [32], would contribute to SiH 2 removal. The non-observation of a quadratic dependence of k obs on [NH 3 ] can therefore be taken as further evidence against the direct reaction of SiH 2 with NH 3 .…”
Section: Ab Initio Calculations For Sih 2 +Nh 3 and Further Mechanistmentioning
confidence: 93%
“…The true values for the second order rate constants of this reaction are almost certainly smaller than we are observing probably by as much as an order of magnitude (at 10 Torr). It is also probable that a catalysed process, involving two molecules of NH 3 , by analogy with findings in the SiH 2 +H 2 O reaction system [32], would contribute to SiH 2 removal. The non-observation of a quadratic dependence of k obs on [NH 3 ] can therefore be taken as further evidence against the direct reaction of SiH 2 with NH 3 .…”
Section: Ab Initio Calculations For Sih 2 +Nh 3 and Further Mechanistmentioning
confidence: 93%
“…Similar to carbenes, most of silylenes and germylenes can function as Lewis acid or Lewis base, in which the vacant p orbital is responsible for electrophilic character (Lewis acid), while the non-bonding electron pair can act as the nucleophilic (Lewis base) attack region [77]. The activation reactions of some small inorganic and organic compounds by Lewis acid-base addition reactions, such as NO [91,98], NH 3 [103,110], CO [93], CO 2 [94,108], O 2 [91,102], Cl 2 [91] H 2 O [95,96,[103][104][105]110], C 2 H 4 [106,112], and C 2 H 2 [107] with silylenes and germylenes have been investigated experimentally. The insertion reactions of silylenes or germylenes into C-H, C-Cl, C-Br, and O-H bonds of small molecules, for example, CH 4 [110,111], CCl 4 [100,101], and CBr 4 [100] etc., have also been studied by the density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of silylenes and germylenes with alcohols have been reported to take place via the activation of O-H bond to generate the corresponding alkoxyhydrosilane [33,35,46]. In fact, activation of O-H of water molecule can also proceed with silylenes [67,95,96,103]. Similar mechanism exists for carbenes as well [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first gaseous water‐catalyzed SiH 2 reaction has been experimentally and theoretically shown that addition of another H 2 O can significantly reduce the reaction barrier 9. Herein, we discuss the catalysis effect on the C 2 F + H 2 O reaction.…”
Section: Resultsmentioning
confidence: 95%